2011
DOI: 10.1590/s0066-782x2011001200021
|View full text |Cite
|
Sign up to set email alerts
|

Angioplastia coronariana versus cirurgia de revascularização: revisão de estudos randomizados

Abstract: We carried out a review that included results of randomized trials that made a comparison between percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG). The 25 selected trials involved 12,305 patients, 11,103 of whom were from studies in patients with multi-vessel disease and 1,212 were from studies in patients with single lesion of the left anterior descending (LAD). In the studies of multivessel disease patients, the PCI showed a trend towards lower early mortality (1.2% versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
1
0
3
Order By: Relevance
“…Considering the worldwide evidence that indicates a reduced number of surgical revascularizations compared with a simultaneous and significant increase in the percutaneous approaches, with or without coronary stent implantation [ 16 ] , concepts such as cost-effectiveness and ischemia-free survival or re-intervention justify the real concern of the assistant cardiologist regarding the appropriate clinical monitoring of these patients. In this context, a recent review published by Andrade et al [ 17 ] demonstrated that the comparison between percutaneous and surgical revascularization approaches is controversial even when it is based only on the most robust randomized clinical trials and mainly when it includes studies conducted in different stages of the interventional cardiology (period of exclusive use of balloon catheters compared with the subsequent advent of conventional coronary stents and, more recently, drug-eluting stents) and studies using different surgical techniques, considering whether the myocardial revascularization is associated to the cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the worldwide evidence that indicates a reduced number of surgical revascularizations compared with a simultaneous and significant increase in the percutaneous approaches, with or without coronary stent implantation [ 16 ] , concepts such as cost-effectiveness and ischemia-free survival or re-intervention justify the real concern of the assistant cardiologist regarding the appropriate clinical monitoring of these patients. In this context, a recent review published by Andrade et al [ 17 ] demonstrated that the comparison between percutaneous and surgical revascularization approaches is controversial even when it is based only on the most robust randomized clinical trials and mainly when it includes studies conducted in different stages of the interventional cardiology (period of exclusive use of balloon catheters compared with the subsequent advent of conventional coronary stents and, more recently, drug-eluting stents) and studies using different surgical techniques, considering whether the myocardial revascularization is associated to the cardiopulmonary bypass.…”
Section: Introductionmentioning
confidence: 99%
“…A tendência a maior mortalidade precoce encontrada nos pacientes cirúrgicos aparece no Registro do Estado de Nova York, com alguma melhora na era dos stents (SERRUYS et al, 2003;ZHANG et al, 2003). Os piores resultados da mortalidade precoce cirúrgica nos primeiros estudos da era stent deviam-se à gravidade dos pacientes, pois a maior parte deles, com angina instável de alto risco, eram frequentemente tratados por cirurgia; atualmente, os pacientes são encaminhados para angioplastia com stent (ANDRADE et al, 2011). Quanto à mortalidade intermediária, os dados são extremamente consistentes: não há nenhuma diferença em um ano entre angioplastia e cirurgia (BRAVATA et al, 2007).…”
Section: Revisão Da Literaturaunclassified
“…Também não foi encontrada diferença significativa na mortalidade tardia, particularmente na era stent, ao contrário do que era visto na era do balão (HOFFMAN et al, 2003). As hipóteses para essa melhora seriam o progresso na técnica intervencionista, permitindo tratar de forma mais completa e segura as obstruções, assim como progressos no tratamento clínico, com antiagregantes plaquetários e hipolipidemiantes mais potentes (ANDRADE et al, 2011). A tendência à maior incidência de acidente vascular cerebral (AVC) no grupo cirúrgico já havia sido sugerida anteriormente, tendo alcançado significância estatística no SYNTAX, devido à maior manipulação da aorta durante procedimento cirúrgico (BRAVATA et al, 2007;MORICE et al, 2010), apesar da análise individualizada dos dados sugerir que os melhores resultados da cirurgia foram justamente nos estudos que utilizaram técnica convencional, ou seja, esternotomia mediana e cirurgia com circulação extracorpórea (CEC) com manipulação maior da aorta (SIMA, LAUSANNE e MASS I), e os piores nos que utilizaram técnicas minimamente invasivas e sem CEC, com menor manipulação da aorta (HONG et al, 2005;HUEB et al, 1995;KIM et al, 2005).…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation